2022
DOI: 10.1101/2022.08.11.503600
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Beyond Linear Neural Envelope Tracking: A Mutual Information Approach

Abstract: The human brain tracks the temporal envelope of speech, which contains essential cues for speech understanding. Linear models are the most common tool to study neural envelope tracking. However, information on how speech is processed can be lost since nonlinear relations are precluded. As an alternative, mutual information (MI) analysis can detect both linear and nonlinear relations. Yet, several different approaches to calculating MI are applied without consensus on which approach to use. Furthermore, the add… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…Envelope processing and auditory abilities in general have received limited attention in aphasia research over the past decades. Nevertheless, both the current paper and recent literature convincingly demonstrate the impairment of such fundamental auditory processes in aphasia at the behavioral (Kries et al, 2023b) and neural (De Clercq et al, 2023a;Kries et al, 2023a) level. Efficient rise time processing is, however, critical for higher-level speech comprehension as well, as these carry critical cues for detecting and segmenting phonemes, syllables and words (Goswami et al, 2011;Hämäläinen et al, 2012;Oganian and Chang, 2019).…”
Section: Behavioral Correlates Of Impaired Neural Envelope Tracking I...supporting
confidence: 73%
See 1 more Smart Citation
“…Envelope processing and auditory abilities in general have received limited attention in aphasia research over the past decades. Nevertheless, both the current paper and recent literature convincingly demonstrate the impairment of such fundamental auditory processes in aphasia at the behavioral (Kries et al, 2023b) and neural (De Clercq et al, 2023a;Kries et al, 2023a) level. Efficient rise time processing is, however, critical for higher-level speech comprehension as well, as these carry critical cues for detecting and segmenting phonemes, syllables and words (Goswami et al, 2011;Hämäläinen et al, 2012;Oganian and Chang, 2019).…”
Section: Behavioral Correlates Of Impaired Neural Envelope Tracking I...supporting
confidence: 73%
“…Among various disorders, neural tracking has found application in the study of aphasia, a language disorder commonly caused by a stroke in the language-dominant left hemisphere of the brain (Papathanasiou and Coppens, 2017). In response to narratives, individuals with post-stroke aphasia (IWA) display decreased neural tracking of the envelope and linguistic speech representations (Kries et al, 2023a;De Clercq et al, 2023a, 2024b. Neural tracking measures further predicted aphasia at the individual level (De Clercq et al, 2023b), with prediction accuracy almost entirely driven by envelope tracking rather than linguistic tracking (De Clercq et al, 2024b).…”
Section: Introductionmentioning
confidence: 99%
“…Once neural tracking in aphasia is better understood, the application potential of this method could be manifold. A study that is currently in preparation found that IWA can be distinguished from healthy controls with 83% accuracy based on neural envelope tracking with mutual information of only 5 to 7 minutes of EEG data (De Clercq et al, 2023). Looking a step further into the future, an aphasia diagnosis based on processing levels of different speech representations could complement behavioral diagnosis and inform speech-language pathologists further which functions should be trained in therapy.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…Once neural tracking in aphasia is better understood, the application potential of this method could be manifold. A study that is currently in preparation found that IWA can be distinguished from healthy controls with 83% accuracy based on neural envelope tracking with mutual information of only 5–7 min of EEG data (De Clercq et al, 2023). Looking a step further into the future, an aphasia diagnosis based on processing levels of different speech representations could complement behavioral diagnosis and inform speech‐language pathologists further which functions should be trained in therapy.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…healthy controls with 83% accuracy based on neural envelope tracking with mutual information of only 5-7 min of EEG data(De Clercq et al, 2023). Looking a step further into the future, an aphasia diagnosis based on processing levels of different speech representations could complement behavioral diagnosis and inform speech-language pathologists further which functions should be trained in therapy.Test-retest practice effects (i.e., improved performance on repeated tests due to remembering items or training test-specific skills) could be avoided during therapy follow-up.…”
mentioning
confidence: 99%